The Correlation of Working Posture toward Complaints of Musculoskeletal Disorders on Pipeline Installation Workers - Auliya Vanissa; Y. Denny A. Wahyudiono; Nungki Marlian Yuliadarwati; Tri Martiana; Gandhi Hartoyo (The Indonesian Journal of Occupational Safety and Health, 2022)
Introduction: Unergonomic working posture is one of the causes of musculoskeletal disorders. Musculoskeletal disorders (MSDs) can be affected by factors such as working hours, age, and posture. If the working posture is not done correctly, it may cause disorders of the muscles, bones, tendons, and nervous system. This study aims to analyze the correlation of working posture toward complaints of musculoskeletal disorders (MSDs) on pipeline installation workers of a state-owned water utility company (PDAM). Methods: The design of this study was a descriptive qualitative with a cross-sectional design. The sample in the study consisted of 30 workers selected by a total sampling method. The variables in this study were working postures whose data were obtained using the Quick Exposure Checklist (QEC) instrument and musculoskeletal disorders (MSDs) whose data were obtained using the Nordic Body Map (NBM) instrument. The data analysis used in this study was a gamma correlation test. Results: According to the results obtained, for actions that need to be investigated further and changed soon, 55.6% had a high category, and 44.4% had a very high category of musculoskeletal complaints. Meanwhile, in the category of acts that need to be investigated and changed immediately, 15.4% had moderate musculoskeletal complaints, 15.4% had high musculoskeletal complaints, and 69.2% had very high musculoskeletal complaints. According to the results of the correlation test between the working posture variable and the symptoms of musculoskeletal disorders (MSDs), the significance value obtained was 0.000 and the coefficient value obtained was 0.752. Conclusion: There was a significant and strong positive relationship between the two variables, that is, the higher the working posture value, the higher the main complaints of musculoskeletal disorders (MSDs).Keywords: work posture, musculoskeletal disorders (MSDs), pipeline installation workers